Advancements in precast concrete sandwich panels for load bearing structures - Kumar, Pushpender; Nighot, Nikhil Sanjay; Kumar, Rajesh; sharma, Surabhi; Kirgiz, MS; Goyal, Arpit (Applied Engineering and Technology, 2024)
Concrete sandwich panels consist of two concrete layers separated by an insulating foam core, offering thermal insulation, structural strength, and fire resistance. This study investigates sustainable precast concrete sandwich panels made with industrial waste materials like limestone slurry, quarry waste, and basalt fiber as shear connectors. The research evaluates the flexural and axial strength behavior of these panels and explores strategies to improve their structural performance. The panels were fabricated with outer concrete layers, an expanded polystyrene (EPS) insulation core, and basalt fiber connectors. Flexural tests using four-point bending and axial compression tests were conducted on panels with varying concrete layer thicknesses and basalt fiber widths. Findings revealed panels with thicker outer concrete layers (35mm) and wider basalt fiber connectors (11.5mm) exhibited higher cracking loads, load-hardening behavior, and increased ductility compared to thinner layers and narrower connectors. The axial test showed premature failure at the top and bottom quarters. Thicker concrete layers and wider basalt fiber connectors enhanced crack control, load distribution, and ductile behavior under flexural loading. Strengthening measures like additional reinforcement, proper anchorage detailing, and increased shear reinforcement at the end regions are recommended to improve axial load-bearing capacity and prevent premature end failures.  The PCSP demonstrated up to 40% cost savings over commercial products while providing better thermal insulation than conventional brick masonry due to the EPS core. Overall, the study promotes developing sustainable, energy-efficient, and cost-effective load-bearing sandwich panel systems.